1992
DOI: 10.1111/j.1651-2227.1992.tb12187.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood T and B lymphocyte subpopulations in healthy infants and children

Abstract: Monoclonal antibodies and flow cytometry are now used routinely in the diagnosis of many malignant diseases and primary and secondary immunodeficiency states. Technical advances have improved the identification of blood lymphocyte subsets and reliable normal values are now obtainable. Such values have been reported for adults but not for children. We report both absolute and percentage normal values for lymphocytes and their subsets in infants and children of different ages. Our findings show that the absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 16 publications
7
37
1
3
Order By: Relevance
“…Prevalence of memory/effector cells (CD45RO) relative to naïve T cells (CD45RA) is indicative of immune maturation, which is in accordance with previous observations that breastfed infants display immunophenotypic changes consistent with greater maturity in the development of their immune system (Hawkes et al, 1999a). The relative frequencies of each lymphocyte population in this study fall within the ranges reported elsewhere for the relevant age group (Erkeller-Yuksel et al, 1992;Heldrup et al, 1992;ComansBitter et al, 1997). Collectively, these data suggest that reported changes in immune function in response to dietary NT are not mediated by shifts in the major T-and B-cell populations.…”
Section: Discussionsupporting
confidence: 79%
“…Prevalence of memory/effector cells (CD45RO) relative to naïve T cells (CD45RA) is indicative of immune maturation, which is in accordance with previous observations that breastfed infants display immunophenotypic changes consistent with greater maturity in the development of their immune system (Hawkes et al, 1999a). The relative frequencies of each lymphocyte population in this study fall within the ranges reported elsewhere for the relevant age group (Erkeller-Yuksel et al, 1992;Heldrup et al, 1992;ComansBitter et al, 1997). Collectively, these data suggest that reported changes in immune function in response to dietary NT are not mediated by shifts in the major T-and B-cell populations.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the expressed mRNA was analyzed to distinguish between the IgM and the IgG repertoire. Otherwise, the small, but relevant subset of IgG-expressing B cells might be overlooked within the predominant IgM-expressing B cell population of neonates (17). This study presents three novel observations about the evolution of the IgH chain gene repertoire during early human development: 1) Premature exposure to extrauterine environmental Ags did not result in a more adult-like pattern of gene segment usage.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have demonstrated that irnmature erythrocytes are not adequately removed by gradients and these yield a falsely elevated number of cells not marking with lymphoid markers (18). This may explain the low percentage of CU45 + cells observed in the immunophenotyping of normal pediatric blood by Heldrup et al (14).…”
Section: Peripheral Bloodmentioning
confidence: 95%